The Glucocorticoid Receptor in Osterix‐Expressing Cells Regulates Bone Mass, Bone Marrow Adipose Tissue, and Systemic Metabolism in Female Mice During Aging. (24th November 2021) - Pierce, Jessica L; Sharma, Anuj K; Roberts, Rachel L; Yu, Kanglun; Irsik, Debra L; Choudhary, Vivek; Dorn, Jennifer S; Bensreti, Husam; Benson, Reginald D; Kaiser, Helen; Khayrullin, Andrew; Davis, Colleen; et al.
ABSTRACT: Hallmarks of aging‐associated osteoporosis include bone loss, bone marrow adipose tissue (BMAT) expansion, and impaired osteoblast function. Endogenous glucocorticoid levels increase with age, and elevated glucocorticoid signaling, associated with chronic stress and dysregulated metabolism, can have a deleterious effect on bone mass. Canonical glucocorticoid signaling through the glucocorticoid receptor (GR) was recently investigated as a mediator of osteoporosis during the stress of chronic caloric restriction. To address the role of the GR in an aging‐associated osteoporotic phenotype, the current study utilized female GR conditional knockout (GR‐CKO; GR fl/fl :Osx‐Cre+) mice and control littermates on the C57BL/6 background aged to 21 months and studied in comparison to young (3‐ and 6‐month‐old) mice. GR deficiency in Osx‐expressing cells led to low bone mass and BMAT accumulation that persisted with aging. Surprisingly, however, GR‐CKO mice also exhibited alterations in muscle mass (reduced % lean mass and soleus fiber size), accompanied by reduced voluntary physical activity, and also exhibited higher whole‐body metabolic rate and elevated blood pressure. Moreover, increased lipid storage was observed in GR‐CKO osteoblastic cultures in a glucocorticoid‐dependent fashion despite genetic deletion of the GR, and could be reversed via pharmacological inhibition of the mineralocorticoid receptor (MR). These findings provide evidence of a role for the GR (and possibly the MR) in facilitating healthy bone maintenance with aging in females. The effects of GR‐deficient bone on whole‐body physiology also demonstrate the importance of bone as an endocrine organ and suggest evidence for compensatory mechanisms that facilitate glucocorticoid signaling in the absence of osteoblastic GR function; these represent new avenues of research that may improve understanding of glucocorticoid signaling in bone toward the development of novel osteogenic agents. © 2021 American Society for Bone and Mineral Research (ASBMR).